The impact of ageing mechanisms on musculoskeletal system diseases in the elderly - Cai, Yijin; Han, Zhongyu; Cheng, Hong; Li, Hongpeng; Wang, Ke; Chen, Jia; Liu, Zhi-Xiang; Xie, Yulong; Lin, Yumeng; Zhou, Shuwei; Wang, Siyu; Zhou, Xiao; et al. (Frontiers in Immunology, 2024)
Ageing is an inevitable process that affects various tissues and organs of the human body, leading to a series of physiological and pathological changes. Mechanisms such as telomere depletion, stem cell depletion, macrophage dysfunction, and cellular senescence gradually manifest in the body, significantly increasing the incidence of diseases in elderly individuals. These mechanisms interact with each other, profoundly impacting the quality of life of older adults. As the ageing population continues to grow, the burden on the public health system is expected to intensify. Globally, the prevalence of musculoskeletal system diseases in elderly individuals is increasing, resulting in reduced limb mobility and prolonged suffering. This review aims to elucidate the mechanisms of ageing and their interplay while exploring their impact on diseases such as osteoarthritis, osteoporosis, and sarcopenia. By delving into the mechanisms of ageing, further research can be conducted to prevent and mitigate its effects, with the ultimate goal of alleviating the suffering of elderly patients in the future.